(untitled) (Hawaii, 1994)
The objecttives of this symposium were to provide a forum to present research result in socioeconomics of aquaculture and to exchange information and ideas of socioeconomics research in aquaculture, to identify socioeconomic constraints of aquaculture development,...
Keywords: Fish culture; Economic aspects